Knowledge Management and its Implementation in the Human Resources Unit of the Palembang Muhammadiyah Hospital - Gladdays Naurah; Diana Pratiwi; Tia Ariani Salsabila; Rino Orleans Adam; Muhammad Nurrochman; Vip Paramarta (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research aims to describe Knowledge Management and its implementation in the Human Resources Unit of the Palembang Muhammadiyah Hospital. Based on this research, qualitative descriptive techniques are used which are connected to literature studies. The qualitative approach is usually referred to as a postpositivistic method because it is based on postpositivistic theory. The research strategy implemented has the initial aim of producing this article by providing research starting point for academics interested in this topic. Research resultThe application of KM is needed for an organization or company that empowers quite a lot or large human resources. And KM can help a company process the knowledge it has well so that this knowledge can be shared equally by every individual involved in an organization and company. By implementing this, an organization or company can advance in the field of information and knowledge processing.People, leadership, technology, organization, learning are important factors that must be considered so that an organization's knowledge management can be implemented optimally.New information and communication technologies, Integration of knowledge processes to organization's processes, Management support, Learning culture, Qualification of employees, Corporate cultureis according to several case studies with a focus on small and medium companies which are known to be critical success factors for implementing KM processes.